Mining and biodiversity: are they compatible? - Majer, Jonathan (Springer, 2014)
The growth and success of the Western Australian mining, oil and gas industries has brought massive financial benefits to the state, and to the nation as a whole. But what has been the impact on Australia’s biodiversity? Application of the Biodiversity Integrity Index (BII) to five major land uses in Western Australia (namely, agricultural clearing, rangeland grazing, urbanisation, transport corridors and mining) results in a figure that indicates the degree of alienation (‘product of loss times area affected’) caused by each type of land use. An examination of the extent of this land alienation indicates that mining has by far the least impact (the state being considered as a whole). However, it should be remembered that there are multiplier effects impacting outside the mined area, and that mining also repeatedly targets particular geological formations with their associated ecosystems. This means that impacts are cumulative through time, and points to the fact that certain ecosystems will increasingly be threatened. These factors, and the escalating pace of minesite development, suggest that it is time to ask: what is important to us in Australia?